KOREKSI ATAS : PERSPEKTIF “ONTOLOGI” DALAM FILSAFAT ILMU (Telaah Atas Buku Filsafat Ilmu Tulisan Jujun S. Suriasumantri) - Abdul Ghafir (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2018)
Each discipline of Sciences has a scope of discussion on the basis of epistemology which is the reference in the discussion. Something particular epistemology may be a reference from some science or may be di erent epistemology. . However, the message to be conveyed by a particular science, should be di erent, at least in terms of the speci cations and provisions applicable in that science, including in terms of the terminology used. If this is ignored, it will cause confusion of understanding and in turn the message to be delivered discipline does not reach the target, even it raises the problem. Moreover, between Philosophy and Science, there is clearly a signi cant epistemological di erence. If Philosophy departs from the spirit of contemplative thinking that is not legitimated with the involution of any discipline, in a free and underserved discourse. While Science departs from certain rules, even depended on a particular discipline. is means that speaking of Philosophy must be independent of any discipline, speci cation and legitimacy context. is paper attempts to describe some of the terms applicable in Philosophy of Sciences which should not have happened and is legitimate to be corrected, otherwise it can be interpreted to straighten understanding. Namely the use of the term “Philosophy” which is quali ed by the term “Science” and the term “ontology” on the book Philosophy of Science (A Popular Introduction), by Jujun S. Suriasumantri published by: Pustaka Sinar Harapan, Jakarta, 1996.